2016
DOI: 10.1039/c5cp04721h
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on electrosynthesis, morphological and electrochromic properties of a nitrogen analog of PEDOT

Abstract: A new nitrogen analog of 3,4-ethylenedioxythiophene (EDOT), N-methyl-3,4-dihydrothieno[3,4-b][1,4]oxazine (MDTO), was electropolymerized in different solvents (deionized water, acetonitrile, and propylene carbonate) using LiClO4 as the electrolyte. The structure and performance of as-prepared PMDTO polymers were systematically studied by cyclic voltammetry, UV-vis spectroscopy, FT-IR, SEM, thermogravimetry, spectroelectrochemistry and electrochromic techniques. To our surprise, solvents had a major influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…Moreover, high viscosity of PC also slows down the speed of monomer and oligomers during electropolymerization. 34,36 This indicates that MeCN is more suitable medium for polymerization of EDOS as compared to PC similar to previously reported polymerization behaviour of MDTO 36 and terthiophene. 47 In addition to solvent, electropolymerization of EDOS is also inuenced by supporting electrolyte.…”
Section: Electropolymerization In Different Solvent-electrolyte Mediasupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, high viscosity of PC also slows down the speed of monomer and oligomers during electropolymerization. 34,36 This indicates that MeCN is more suitable medium for polymerization of EDOS as compared to PC similar to previously reported polymerization behaviour of MDTO 36 and terthiophene. 47 In addition to solvent, electropolymerization of EDOS is also inuenced by supporting electrolyte.…”
Section: Electropolymerization In Different Solvent-electrolyte Mediasupporting
confidence: 88%
“…This difference in the electrochemical behaviour due to solvents is explained by slow and smooth growth of longer polymer chains in PC which results in faster electron transfer. 36,51 A similar trend was noticed in the CV of PMDTO lms prepared in MeCN and PC. 36 It is noteworthy to mention that the redox behaviour of PEDOS lms were also considerably inuenced by supporting electrolytes.…”
Section: Electrochemistry Of Pedos Lmssupporting
confidence: 77%
See 1 more Smart Citation
“…Not only that, it can be used to study the composition of a compound in which absorption spectra are known. Furthermore, it is used to characterize optical devices such as electrochromic devices (164)(165)(166). In this method, determine the intensity of light ( ) passing through a material and then compare it to the intensity of the light ( ) before it passes through the material at a different wavelength.…”
Section: Absorbance Spectroscopymentioning
confidence: 99%
“…Different strategies can be employed to produce such structures, but the emphasis has been given to techniques that allow controlling molecular architectures, including Layer-by-Layer [7] physical evaporation, [8] Langmuir and Langmuir-Blodgett films [9][10][11][12]. In these cases, different supramolecular architectures can be achieved by tuning experimental conditions, such as i) deposition methods [1] ii) thermal annealing [13] iii) solvent interaction [14,15] among others. For instance, Xiao et al [16] have shown the influence of different solvents on the morphology and crystallinity of poly(3-hexylthiophene) (P3HT) thin films.…”
Section: Introductionmentioning
confidence: 99%